User satisfaction towards rail public transport services in Sabah by Sabah State Railway / Aiman Hafizi Mohd Rozi - Mohd Rozi, Aiman Hafizi (2016)
This study entitled User Satisfaction Towards Rail Public Transport Services in Sabah By Sabah State Railway. The aim of this research study to investigate user satisfaction towards train services that been provided that stretch from the first station at Station Sembulan to the last station at Station Tenom. This study should be able to obtain deep analysis and understanding about user satisfaction towards train services. This study contains information on the brief history of the company and route map. This research is based o a survey using a set of questionnaire of 23 questions. In this study, descriptive research been used in order to answered and described various characteristic in a situation. The convenience sampling technique was used in this research whereby 100 respondent are randomly selected whether the respondent in the train and at the train station. Secondary data was used in this research where most of the information come from books, journal, internet and the company itself. Information was collected through questionnaires. The data was analyzed and been measured using SPSS or specific using Kruskal Wallis, Mann-Whitney and cross tabulation in order to answer the objectives of this research.